Preclinical evaluation of a bispecific low-molecular heterodimer targeting both PSMA and GRPR for improved PET imaging and therapy of prostate cancer - Eder, Matthias; Schäfer, Martin; Bauder‐Wüst, Ulrike; Haberkorn, Uwe; Eisenhut, Michael; Kopka, Klaus (The prostate, 2014)
BACKGROUND It has recently been reported that metastases of prostate cancer usually show highly heterogeneous or partly lost prostate-specific membrane antigen (PSMA) expression. In order to image and treat both PSMA positive and negative tissues PSMA targeting probes need to be extended by a further specificity. Since prostate cancer cells usually express both PSMA and gastrin-releasing peptide receptor (GRPR) a bispecific low-molecular heterodimeric molecule, addressing both targets at the same time, may significantly improve prostate cancer imaging and therapy. METHODS The nonapeptide BZH3 representing the GRPR binding part was combined with the urea-based PSMA inhibitor Glu-urea-Lys(Ahx)-HBED-CC. The syntheses of the compounds were performed according to standard Fmoc-solid phase peptide synthesis. The binding properties were analyzed by competitive cell binding and internalization experiments. The in vivo targeting properties were investigated by means of biodistribution studies. RESULTS Cell binding experiments revealed high binding affinities to both GRPR and PSMA expressing cell lines. The heterodimer bound with IC50-values essentially matching the IC50 values of the respective monomers (25.0 ± 5.4 nM for PSMA and 9.0 ± 1.8 nM for GRPR, respectively). In vivo, the heterodimer showed dual targeting of PSMA (5.4%ID/g for PSMA-positive tumors) and GRPR receptors (3.3% ID/g for GRPR-positive tumors) while exhibiting fast pharmacokinetic properties. The clearance from background was comparable to the monomeric PSMA-targeting reference. CONCLUSIONS The heterodimeric molecule is a promising agent for PET imaging of primary and recurrent prostate cancer covering two receptor entities which might lead to an improved diagnostic sensitivity and therapeutic efficiency. Prostate 74:659-668, 2014. © 2014 The Authors. The Prostate published byWiley Periodicals, Inc.
Gesehen am 02.09.2020